Oral and vaginal microbiota in selected field mice of the genus Apodemus: a wild population study - Matějková, Tereza; Hájková, Petra; Stopková, Romana; Stanko, Michal; Martin, Jean-François; Kreisinger, Jakub; Stopka, Pavel (Scientific reports, 2020)
Animal-associated microbiota is expected to impose crucial effects on the host's fitness-related performance, including reproduction. Most research to date has focused on interactions between the host with its gut microbiota; however, there remain considerable gaps in knowledge regarding microbial consortia in other organs, including interspecific divergence, temporal stability, variation drivers, and their effects on the host. To fill these gaps, we examined oral and vaginal microbiota composition in four free-living mouse species of the genus Apodemus, each varying in the degree of female promiscuity. To assess temporal stability and microbiota resistance to environmental change, we exposed one of the species, Apodemus uralensis, to standardized captive conditions and analyzed longitudinal changes in its microbiota structure. Our results revealed the existence of a "core" oral microbiota that was not only shared among all four species but also persisted almost unchanged in captivity. On the other hand, vaginal microbiota appears to be more plastic in captive conditions and less species-specific in comparison with oral microbiota. This study is amongst the first to describe oral microbiota dynamics. Furthermore, the vaginal microbiota results are especially surprising in light of the well-known role of stable vaginal microbiota as a defense against pathogens. The results indicate the existence of diverse mechanisms that shape each microbiota. On the other hand, our data provides somewhat ambiguous support for the systematic effect of phylogeny and social system on both oral and vaginal microbiota structures.
Keywords: vagina; Sequence Analysis, DNA; Bacteria; orgánová specificita; Mice; Organ Specificity; Microbiota; mikrobiota; ženské pohlaví; zvířata; High-Throughput Nucleotide Sequencing; fylogeneze; Mouth; vysoce účinné nukleotidové sekvenování; myši; ústa; sekvenční analýza DNA; Female; Phylogeny; Vagina; Animals